Physics studies of ADITYA & ADITYA-U tokamak plasmas using spectroscopic diagnostics. (7th February 2022) - Manchanda, R.; Chowdhuri, M.B.; Ghosh, J.; Ramaiya, N.; Yadava, N.; Patel, S.; Shukla, G.; Shah, K.; Dey, R.; Jadeja, K.A.; Patel, K.M.; Tanna, R.L.; et al.
Abstract: Several spectroscopic diagnostics encompassing the spectral emission range from the x-ray to near infrared (NIR) have been developed, installed and operated for diagnosing and physics studies in the ADITYA and ADITYA-U tokamaks. The recycling and impurity influxes and plasma Z eff after lithium (Li) coating have been studied using a PMT (photomultiplier tube)-filter based system by capturing H α, O 1+, C 2+, and visible continuum emissions. Significant reduction in the Z eff values has been observed in the discharge with the Li coated walls. The measured radial profile of H α emission using a filter-PMT array, has been modelled using a neutral transport code. The results show substantial contributions from the molecular hydrogen and molecular hydrogen ion dissociation (∼56%) and charge-exchange (∼30%) processes in the measured H α emission. Furthermore, a high-resolution, 1 m spectrometer with charge coupled device detector capable of multi-track measurements, has been used to study impurity transport, neutral and ion temperature and intrinsic plasma rotation. By modelling the measured radial profile of O 4+ spectral line emission using an impurity transport code, substantial contribution of edge fluctuations on the oxygen transport has been observed. The toroidal ( u T max ∼ 20 km s −1 in core) and poloidal ( u θ max ∼ 4.5 km s −1 at edge) rotation velocities are measured using C 5+ (529 nm) and C 2+ (464.7 nm) passive line emissions respectively. The measurement of radial profile of toroidal plasma rotation revealed a reversal of rotation direction depending on the electron density content of the ADITYA-U plasmas. The neutral temperature measurements showed a poloidal asymmetry indicating a presence of asymmetrical source of neutral heating. Moreover, the modelling of measured Fe 14+ and Fe 15+ vacuum ultraviolet spectral lines has revealed the neo-classical nature of iron transport in ADITYA core. Fast visible camera images captured the formation of filament structures triggered by interchange instabilities during plasma disruptions.